PENINGKATAN MINAT BELAJAR SISWA MELALUI METODE STORY TELLING DI SDN 1 MALANGJIWAN - Kana Noviana; Siti Rochmiyati (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
Abstract This research aims to describe how to increase and result students' interest in learning Indonesian language class I through the story telling method at SDN 1 Malangjiwan. This type of research is Classroom Action Research (PTK) which is carried out collaboratively and participatively. The subjects of this research were 22 class I students at SDN 1 Malangjiwan, with 12 man students and 10 women students. This research was carried out in November 2023 at SDN 1 Malangjiwan, Kebonarum, Klaten Regency. This research was carried out in two cycles, each cycle there were two meetings. Research data was obtained from questionnaires, observations and interviews. Data analysis was carried out descriptively qualitatively and quantitatively. The results of the research show that the use of the story telling method can increase the interest in learning of class I students at SDN 1 Malangjiwan. In cycle I, it showed that 80% (16 students) of class I students obtained a learning interest score ≥ 25 (high learning interest category) and in cycle II there were 85% (17 students) of class I students obtained a learning interest score ≥ 25 (category high interest in learning). In addition, there was an increase in class I students' interest in learning from the pre-cycle showing the number 16.50 in the low learning interest category, in the first cycle showing the number 25.75 in the high learning interest category, and to 26.50 in the High interest in learning in cycle II.